TandemHeart-Assisted Balloon Aortic Valvuloplasty for Acute Transcatheter Aortic Valve Replacement Thrombosis - Elison, David (JACC Case Rep, 2020)
The patient in this report had a catastrophic case of transcatheter aortic valve replacement–related valve thrombosis manifesting within 1 month of valve implantation that was complicated by acute heart failure and cardiogenic shock. Anticoagulation and thrombolytic agents were not successful, and the patient was treated with TandemHeart (Cardiac Assist, Pittsburgh, Pennsylvania)–supported balloon aortic valvuloplasty and cerebral embolic protection. (Level of Difficulty: Advanced.)